Dissociation of Extinction and Behavioral Disinhibition: The Role of NMDA Receptors in the Pigeon Associative Forebrain during Extinction - Lissek, Silke (J Neurosci, 2003)
Extinction is a unique learning process that requires the alteration of stimulus-response associations such that the organism ceases to respond to a previously rewarded stimulus. Extinction is mostly studied with fear conditioning and is impaired by lesions of the prefrontal cortex as well as by blockade of NMDA receptors in the amygdala. Because previous tasks could not clearly disambiguate extinction from behavioral disinhibition, the underlying process was difficult to define. In this study, we examined the possible role of NMDA receptors and the pigeon “prefrontal cortex,” the neostriatum caudolaterale (NCL), for extinction of appetitive instrumental conditioning. We used a new design that discerns extinction from behavioral disinhibition. Our results demonstrate that NCL lesions cause deficits neither in extinction learning nor in extinction recall. However, blockade of NMDA receptors in the pigeon NCL by dl-AP-5 drastically impairs extinction learning without producing behavioral disinhibition or deficits in extinction recall. We suggest that NMDA receptors in the NCL contribute to the establishment of a learning process that selectively signals the change in value of the instrumental stimulus. Although NCL plays a key role for extinction learning, other structures can subsume similar functions after postlesional regeneration.